O encontro como categoria teológica a partir da obra de Alfonso López Quintás - Madureira, José Gabriel Perissé (2018)
The definition of encounter, according to the Spanish philosopher Alfonso López Quintás, is the starting point for to draw around the encounter as a theological category. The purpose was to clearly identify the essential characteristics and the fruits of the interpersonal encounter, as well as the discovery of the values and the longing for transcendence. When contrasting the theory of the encounter of López Quintás with the work of different philosophers, theologians and thinkers who focused on the idea of "encounter with God", it is possible to glimpse and make explicit, in the work of this author, the main features of a legitimate theology of the encounter.